Assessment of Adolescent Student's Knowledge toward Premenstrual Syndrome in Nursing Secondary Schools at Al-Diwanyia Governorate - Fatin Abdul Amir Al-Saffar; Fadia Hussein Ali (Kufa Journal for Nursing Sciences)
Objective: to assess Adolescent Student's Knowledge toward Premenstrual Syndrome in Nursing Secondary Schools at Al-Diwanyia Governorate.